Skilling Up to Do Data: Whose Role, Whose Responsibility, Whose Career? - Graham Pryor; Martin Donnelly (International Journal of Digital Curation, 2009)
What are the roles necessary to effective data management and what kinds of expertise are needed by the researchers and data specialists who are filling those roles?Â  These questions were posed at a workshop of data creators and curators whose delegates challenged the DCC and RIN to identify the training needs and career opportunities for the broad cohort that finds itself working in data management â€“ sometimes by design but more often by accident.Â  This paper revisits previous investigations into the roles and responsibilities required by a â€œdata workforceâ€, presents a representative spectrum of informed opinion from the DCC Research Data Management Forum, and makes some recommendations for raising capability, capacity and status.